2017
DOI: 10.1016/j.jsbmb.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols formation: A review of a multifactorial process

Abstract: Highlights1-Heating sterols at 180 °C produced a high extent of oxidation.2-The presence and unsaturation degree of the surrounding lipids protected sterols from oxidation.3-Plant aqueous extracts protected cholesterol from oxidation.4-Greater amounts of campesterol-derived oxidation products were observed, followed by sitosterol, cholesterol and stigmasterol.5-In 5 out of 7 of our studies, 7-keto derivatives were the most abundant oxysterols formed. AbstractDietary sterols are nutritionally interesting compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…As described in the literature the influence of cholesterol oxides on human health deserves some emphasis, because the exogenous cholesterol oxides formed during processing of foods can be potential harmful to health, affecting the cellular metabolism, changing the membrane composition and proprieties, and they are more cytotoxic than cholesterol and are associated with the development of cardiovascular and neurodegenerative diseases, among others, which can cause deleterious effects such as inflammation, atherosclerosis, mutagenic and carcinogenic, and cell death. (Thanan and others ; Laparra and others ; Barriuso and others ; Doria and others ; Kulig and others ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As described in the literature the influence of cholesterol oxides on human health deserves some emphasis, because the exogenous cholesterol oxides formed during processing of foods can be potential harmful to health, affecting the cellular metabolism, changing the membrane composition and proprieties, and they are more cytotoxic than cholesterol and are associated with the development of cardiovascular and neurodegenerative diseases, among others, which can cause deleterious effects such as inflammation, atherosclerosis, mutagenic and carcinogenic, and cell death. (Thanan and others ; Laparra and others ; Barriuso and others ; Doria and others ; Kulig and others ).…”
Section: Resultsmentioning
confidence: 93%
“…However, some authors have demonstrated that sardines also contain high levels of cholesterol (Saldanha and others ; Scherr and others ). These 2 types of compounds, n ‐3 PUFAs and cholesterol, are not chemically stable and this instability is influenced by their chemical structure, the presence of oxygen, light, metal ions, and the processing techniques (heat) used, among other factors (Dantas and others ; Barriuso and others ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of unsaturated fatty acids in the food matrix may accelerate the oxidation of cholesterol, as it generates a pro-oxidant environment, due to the presence of resonance zones, resulting in radicals such as hydroperoxides (Barnaba et al, 2016). However, lipids may compete for oxygen with sterols and reduce sterol oxidation by auto-oxidation (Barriuso, Ansorena, & Astiasarán, 2017).…”
Section: Cholesterol Oxidationmentioning
confidence: 99%
“…Oxysterols are products of enzymatic and non-enzymatic oxidation of cholesterol, its precursors and phytosterols. They can be synthesised endogenously though different pathways, but they also are absorbed from diet, where their amount depends on temperature, oxygen, light exposure, lipid surrounding matrix and presence of antioxidants and water [14]. Oxysterols, which are present in physiological conditions in rather low amounts, are intermediates in cholesterol metabolism to bile acids and steroid hormones.…”
Section: Introductionmentioning
confidence: 99%